Effectiveness of Collaborative Learning for Improving Learners’ Writing Proficiency in English Classrooms - Bhandari, Bhim Lal (Tribhuvan University Journal, 2022)
The success of language teaching and learning depends on collaborative atmosphere between the teachers and students in the class. Collaborative learning is a learner centered approach for language teaching and learning. It engages learners to work collaboratively with teachers. This study aimed at investigating the effectiveness of collaborative learning for improving learners’ proficiency in English classrooms. The study was based on an experimental research design. For this purpose, I selected 50 students from grade 12 in the academic year of 2020.Among them 25 were selected for experimental group while 25 for control group as sample population of the study. Pre-test and post-test items related to writing proficiency were used as the tools for data collection. The study revealed that students of experimental group made better progress in improving writing skill than the students of control group in the post-test which confirmed the effectiveness of collaborative learning in teaching writing. Those who were engaged in free writing in collaboration with each other created better written texts than those who wrote writing texts individually by themselves. Besides, the students of experiment all group obtained 19.42 average score whereas the control group obtained 14.82 average score out of 25. Thus, collaborative learning contributes to improve students’ writing as it assisted them to produce the quality of their writing.